Benefits of implementing IT tools and procedures for the estimation and measurement uncertainty in testing laboratories - Dijmarescu, Maria Cristina (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Destructive and non-destructive testing of materials present a rapid expansion given by the increase in market demand caused by the desire to obtain an increasingly better quality of products. The continuous increase in quality demands leads directly to the need to implement and modernize the techniques, methods, and equipment used for quality control. Consequently, the need for product testing services has a rapid growth. This paper presents the strength and weaknesses of implementing IT tools for the estimation of the measurement uncertainty in testing laboratories and the impact of these tools on the economic part